ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR DALAM LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Riana, Astaris Marga (STIE AUB Surakarta, 2018)
This study aims to determine the effect Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Total Asset Turnover (TAT) either partially or test the model to Profit Growth at the manufacture company in LQ45 which listed on the Indonesia Stock Exchange. The sampling technique used in this research is purposive sampling with some criteria , those are : (1) the manufacture company which include LQ45 2010-2016 period, (2) has a positive profit, (3) and using monetary unit of rupiah. The result of this research shows that the data has fulfill the calssical assumption, such as : no multicollinearity, no autocorrelation, no heteroscedastisity and distributed normally. The results of the partial test (t test) showed only variable Debt to Equity Ratio (DER) the significant effect on Profit Growth. While other variables are Current Ratio (CR), Net Profit Margin (NPM) and Total Asset Turnover (TAT) no significant effect on Profit Growth. The test results are test models show that Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Total Asset Turnover (TAT) jointly significant effect on Profit Growth. The test results demonstrate value of the coefficient of determination Adjusted R Square of 0,153 this means 15,3% of the dependent variable is influenced by the variable independent, while the remaining 87,3% in influenced by other factor not examined in this study.Keywords : Current Ratio (CR), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Total Asset Turnover (TAT), and Profit Growth.